KUNCI MANAJEMEN WAKTU PENGERJAAN TUGAS KELOMPOK DALAM ERA KOLABORASI: BENARKAH SELF EFFICACY DAN SELF REGULATED BERPENGARUH? - Nasriani, Nasriani; Afiah, Nur (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
Time management in group assignments is a key factor in students' academic achievement. However, many students still face challenges in managing their time optimally, which affects team performance quality. This study aims to analyze the influence of self efficacy and self-regulation on students' time management in the context of group assignments. A quantitative research method was employed using a multiple linear regression analysis design. The study sample consisted of 150 active students from IAIN Parepare, selected through a cluster random sampling technique. Data were collected through questionnaires measuring self-efficacy, self-regulation, and time management scales. The results indicate that self-regulation has a significant impact on students' time management, whereas self efficacy does not show a significant effect. These findings suggest that students with strong self-regulation skills are better able to plan, prioritize tasks, and complete assignments on time compared to those who rely solely on self-efficacy. The implications of this study highlight the importance of self-regulation training in academic settings to enhance the effectiveness of group assignments. Therefore, educational institutions are encouraged to develop learning strategies that focus on strengthening self-regulation to support students' academic success.